't Hof van Brabant' als symbool van de Spaanse hofhouding in de Lage Landen (Bulletin KNOB, 1999)
During the reign of Archdukes Albrecht and Isabella the old ducal palace at the Coudenberg in Brussels is transformed. The original fifteenth-century residence had indeed been expanded under Charles V and Maria of Hungary, but still complied with the requirements of the Burgundian-Habsburg court ceremonial.However. after his introduction in Spain - in 1520 under Charles V and especially in 1549, when the court of prince Philip is based on this pattern - this ceremonial is evolving and particularly from the 1560's onwards. Consequently, the residences of Philip II in Spain have a more complex spatial planning, notably with a larger number of public and semipublic spaces preceding the private rooms, where the visitors were received in accordance with their ranks.From 1598 Albrecht and Isabella adjust the Brussels palace to this altered Spanish-Burgundian ceremonial and thus create a truly royal residence, reflecting Albrecht's ambitions in this period. This is the main difference with the court residence in The Hague.